Observations on papaya mealybug, Paracoccus marginatus Williams & Willink (Hemiptera : Pseudococcidae) damag ing some crops in Bangladesh (The Journal of Plant Protection Sciences, 2023)
The papaya mealybug, Paracoccus marginatus Williams and Granara de Willink is a small Hemipteran insect be longing to the Family Pseudococcidae was recorded from immature, mature papaya fruits and foliages from  BCSIR Vegetable Garden during March, 2011. It is a small polyphagous insect pest sucking saps from the attack ing fruits and leaves. P. marginatus passes through egg and three nymphal stages to become adult. Generally, three  and four nymphal instars occur in case of female and male mealybug, respectively. The adults are most active in  warm, dry and humid weather. The male adult mealybugs possess two pairs of wings. Female have no wings and  move by crawling short distances or by being blown in air currents. Female usually lays 100 to 600 eggs. Eggs are  greenish-yellow in colour measuring 0.120 cm diameter and laid in an ovisac that 3-4 times the body length. Eggs  are covered with white waxy substances developed ventrally by the adult female. Egglaying is continued up to 2  weeks and 150-200 eggs were deposited during this period. The life cycle is completed within 29 days at an aver age room temperature of 25 ± 1ºC and 67 ± 5 % RH. The adult life span for male and female were 29 and 27 days,  respectively. P. marginatus is a devastating insect pest causing immense damage to the field crops, vegetables and  ornamental plants of economic importance in Bangladesh perspectives.
Keywords: Papaya mealybug; Paracoccus marginatus; egg; biology; vegetable crops